Exploring the Impact of ESG Practices on Financial Performance: The Moderating Effect of Green Innovation in the Indonesian Energy Sector - Meylani; Martdian Ratna Sari (Universitas Airlangga, 2024)
This study explores the impact of Environmental, Social, and Governance (ESG) practices on the financial performance of energy companies in Indonesia, with green innovation serving as a moderating variable. The research utilizes secondary data from Indonesian energy firms. It employs a cross-sectional analysis to evaluate the relationships between ESG practices, green innovation, and financial performance, measured by Return on Assets (ROA). The findings reveal that ESG practices alone do not significantly affect financial performance. However, when moderated by green innovation, ESG practices positively and significantly impact financial performance. This suggests that green innovation enhances the benefits of ESG initiatives by improving operational efficiency, reducing costs, and bolstering market competitiveness. The study's results have important implications for corporate managers and policymakers, emphasizing the need for integrating green innovation with ESG strategies to achieve sustainable financial growth.